2016
DOI: 10.1097/ijg.0000000000000280
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Retinal Nerve Fiber Layer Thickness, the Mean Deviation, and the Visual Field Index in Progressive Glaucoma

Abstract: Different tests are more likely to detect the progression in different clinical circumstances or stages of glaucoma; these should be taken into consideration when performing the difficult task of progression detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…In another study, Banegas et al supported the role of progression detection using OCT NFL in pre-perimetric and early glaucoma, while they recommended the use of VF testing and optic disc photography for advanced glaucoma monitoring. 12 The findings of the present study are largely in agreement with the above-mentioned studies, with NFL trend analysis showing good progression detection in early to moderate glaucoma, and VF being more useful in identifying progression in moderate to late stages. However, this study also provides novel evidence to support OCT imaging of the macula (specifically GCC) as a useful tool even in the later stages of glaucoma, with similar ability to detect progression as VF.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In another study, Banegas et al supported the role of progression detection using OCT NFL in pre-perimetric and early glaucoma, while they recommended the use of VF testing and optic disc photography for advanced glaucoma monitoring. 12 The findings of the present study are largely in agreement with the above-mentioned studies, with NFL trend analysis showing good progression detection in early to moderate glaucoma, and VF being more useful in identifying progression in moderate to late stages. However, this study also provides novel evidence to support OCT imaging of the macula (specifically GCC) as a useful tool even in the later stages of glaucoma, with similar ability to detect progression as VF.…”
Section: Discussionsupporting
confidence: 91%
“…6,12,34,38,47 Recent studies have focused on the comparison between progression identified with NFL or optic disc OCT imaging and visual fields. 12,38,48 Abe et al suggested that in patients with different glaucoma stages, monitoring NFL with spectral-domain OCT gives a higher chance of detection of disease progression in early stages, while VF testing is more relevant in later stages 38 . In another study, Banegas et al supported the role of progression detection using OCT NFL in pre-perimetric and early glaucoma, while they recommended the use of VF testing and optic disc photography for advanced glaucoma monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…To date, genetic studies on glaucoma have evaluated not only case-control studies on POAG patients but also various endophenotypes such as the IOP, VCDR, disc area, central corneal thickness, VFD, 31,32 and cpRNFLT. 18,20 Among these, the analysis of the cpRNFLT has advantages because of its ability to detect early disease 33,34 ; it also has a linear relationship to the GON, 34 is highly reproducible, 34,35 and has a wider examined area than the HFA regions. Although the changes in VCDR represent the progression of GON and glaucoma diagnosis, 36,37 finer analyses using 768-point cpRNFLT would be a better endophenotype for genetic analysis of POAG.…”
Section: Discussionmentioning
confidence: 99%
“…White-on-white standard automated perimetry (SAP) is the “gold standard” for visual field testing, glaucoma follow-up, and identification of disease progression. However, SAP is highly influenced by patient attention levels and compliance and reveals functional defects only after substantial structural damage has already occurred [ 2 , 3 ]. Modern perimetric tests, such as frequency-doubling technology (FDT) and Pulsar perimetry (PP), have been developed to provide early visual field (VF) defect detection [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%